Analysis of factors that affect purchase intention on mobile Games as a Service (GaaS) - Tiohienritch Fitzdave Irvinne Theodora; Togar Alam Napitupulu (Institute of Computer Science (IOCS), 2023)
Games as a Service (GaaS), also known as live service games, which is a type of cloud computing that is becoming increasingly popular in mobile marketplaces. The research investigates how factors such as Accessibility, Perceived Value, Perceived Credibility, and Intent to Use may influence Purchase Intention in GaaS within the mobile games market, where in-app purchases are rising to generate revenue, and how consumer behaviors correspond to practice and correlates with purchase intention, the urgency to investigate the factors stem from declining revenue for company and lack of customer engagement hence resulting in reduced customer retention and interest. The study's findings indicate that while value, perceived credibility, and accessibility all favorably influence intent to use, intent to use also positively influences intent to buy which helps in quantifying behavioral traits in a a statistical manner and helps understand emotional and other motivators based on the psychological and environmental influence on the customer.